Education, manpower, and economic growth : strategies of human resource development - Harbison, Frederick Harris; Myers, Charles Andrew (New York : McGraw-Hill, 1964)
This book reveals that, less developed countries which have been poor stagnant for centuries are in a state pf revolt against poverty, disease, ignorance, and dominance by stronger nations, and they are no longer disposed to entrust their future exclusively to the forces of the market, the whim of nature, or the judgement of colonial rulers.
"A joint project of the Industrial Relations Section, Princeton University, and the Industrial Relations Section, Massachusetts Institute of Technology, as part of the Inter-university Study of Labor Problems in Economic Development."
Includes bibliographical footnotes and index.
asm 21/01/2019
Loans
Keywords: Labor supply; Education; Economic development